CXC Chemokine Receptor 2 Accelerates Tubular Cell Senescence and Renal Fibrosis via β-Catenin-Induced Mitochondrial Dysfunction - Meng, Ping; Huang, Jiewu; Ling, Xian; Zhou, Shan; Wei, Jingyan; Zhu, Mingsheng; Miao, Jinhua; Shen, Weiwei; Li, Jiemei; Ye, Huiyun; Niu, Hongxin; Zhang, Yunfang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Renal fibrosis is the common pathological feature in various types of CKD. However, the underlying mechanisms are not determined. Our previous reports showed that C-X-C motif chemokine receptor (CXCR) family could have an intimate relationship with the progression of renal fibrosis, however, the specific candidates and detailed mechanisms have not been elucidated. Here, we found that CXCR2 has a potential role in renal fibrosis through inducing β-catenin-activated mitochondrial dysfunction and tubular cell senescence. Among CXCR family, CXCR2 mRNA was increased most in unilateral ureteral obstruction (UUO)-affected kidney. CXCR2 was expressed primarily in tubular cells and colocalized with cellular senescence marker p16INK4A and β-catenin. In UUO mice, administration of SB225002, a CXCR2 receptor blocker, significantly restored mitochondrial function and protected against tubular senescence and renal fibrosis, and inhibited the activation of β-catenin signaling. In unilateral ischemia-reperfusion injury (UIRI) mice, treatment with interlukin-8 (IL-8), the ligand of CXCR2, aggravated the tubular cell senescence and renal fibrosis, further damaged mitochondrial homeostasis, and increased β-catenin activation, whereas, knockdown of p16INK4A inhibited these effects. In vitro, SB225002 inhibited mitochondrial dysfunction, and tubular cell senescence. Furthermore, CXCR2-induced cellular senescence and fibrotic changes were significantly retarded by ICG-001, a blocker for β-catenin signaling. These results suggest that CXCR2 promotes renal fibrosis through inducing β-catenin-activated mitochondrial dysfunction and tubular cell senescence.